Comparison of neutral outgassing of comet 67P/Churyumov-Gerasimenko inbound and outbound beyond 3 AU from ROSINA/DFMS - Luspay-Kuti, A. (Astron Astrophys, 2019)
CONTEXT. Pre-equinox measurements of comet 67P/Churyumov-Gerasimenko with the mass spectrometer ROSINA/DFMS on board the Rosetta spacecraft revealed a strongly heterogeneous coma. The abundances of major and various minor volatile species were found to depend on the latitude and longitude of the nadir point of the spacecraft. The observed time variability of coma species remained consistent for about three months up to equinox. The chemical variability could be generally interpreted in terms of surface temperature and seasonal effects superposed on some kind of chemical heterogeneity of the nucleus. AIMS. We compare here pre-equinox (inbound) ROSINA/DFMS measurements from 2014 to measurements taken after the outbound equinox in 2016, both at heliocentric distances larger than 3 AU. For a direct comparison we limit our observations to the southern hemisphere. METHODS. We report the similarities and differences in the concentrations and time variability of neutral species under similar insolation conditions (heliocentric distance and season) pre- and post-equinox, and interpret them in light of the previously published observations. In addition, we extend both the pre- and post-equinox analysis by comparing species concentrations with a mixture of CO(2) and H(2)O. RESULTS. Our results show significant changes in the abundances of neutral species in the coma from pre- to post-equinox that are indicative of seasonally driven nucleus heterogeneity. CONCLUSIONS. The observed pre- and post-equinox patterns can generally be explained by the strong erosion in the southern hemisphere that moves volatile-rich layers near the surface.